The initial implementation of the transverse bone transport technique in the post-radiation region of the mandible. A pre-clinical in vivo study - Xian Wang; Yuetong Wang; Yuetao Li; Haoyu Lu; Dongqin Mo; Zhiqing Liu; Linjing Gao; Yanfei Zhao; Lixiang Zhao; Yude Huang; Yiyang Fan; Daiyou Wang (BMC Oral Health)
Abstract Background To link the treatment of radiation injury with angiogenesis, and to design and seek a new therapeutic technique for the prevention and treatment of radiation injury. Methods The transverse bone transport device for rabbit mandible was designed and manufactured. Eighteen New Zealand white rabbits were randomly divided into a radiotherapy group and a normal group. The radiotherapy group received 18 Gy of radiation, and the device was implanted two weeks later. After a 7-day incubation period, transverse transportation was performed at a speed of 0.5 circles (0.4 mm) per day, with an 8-day cycle and a total traction distance of 3.2 mm. CBCT, Micro CT, and histological staining were employed to assess the dynamics of movement, osteogenesis, and angiogenesis. Results The transverse bone transport model of rabbit mandible was successfully established. CBCT revealed that the transport height in the normal and radiotherapy groups were 3.24 ± 0.17 mm and 3.22 ± 0.19 mm respectively. Micro CT analysis showed an increase in BV/TV and Tb.N over time, while Tb.Sp decreased; differences in BV/TV existed at 2 weeks but disappeared thereafter; differences in Tb.N and Tb.Sp persisted at 2 and 4 weeks. Histological staining using HE, Masson, and IHC demonstrated good bone maturity accompanied by rich neovascularization, and this was also confirmed by ImageJ software analysis. Conclusions The transverse bone transport was employed for the first time in the radiation-induced mandibular damage, thereby establishing a basis for further investigation into its clinical efficacy, application value, and underlying mechanisms. This breakthrough offers novel prospects for clinical interventions.